Clinical genetic analysis of an adult polyglucosan body disease (APBD) family caused by the compound heterozygous variant of GBE1 p.R156C and deletion exon 3-7 - Zhu, Juan; Yu, Hong-Ping; Zou, Jing; Zhang, Yi-Wu; Han, Xin-Qi; Xu, Zi-Yan; Chen, Li; Chen, Qian; Gao, Mei-Zhu; Xie, Li-Jun; Zhang, Xi-Kui; Luo, Jie-Wei; et al. (Frontiers in Genetics, 2025)
IntroductionAdult Polyglucosan Body Disease (APBD) is a rare, autosomal recessive neurodegenerative disorder that affects both the central and peripheral nervous systems. It is primarily caused by mutations in the Glycogen Branching Enzyme 1 (GBE1) gene. APBD is typically associated with Ashkenazi Jewish populations, though it can occur in other ethnic groups. This study aims to expand the phenotypic and genetic spectrum of APBD, particularly in non-Ashkenazi Jewish patients, and to identify atypical genetic alterations linked to the disease.MethodsA 57-year-old Chinese male (Ⅱ3) presented with a 4-year history of progressive bladder dysfunction, upper and lower motor neuron impairment, sensory loss, and lower limb weakness, leading to difficulty with gait. Genetic testing was performed to identify potential pathogenic variants in the GBE1 gene. A family assessment revealed a sister (Ⅱ5) with the same clinical features. Both patients underwent genetic analysis, which included sequencing and deletion analysis.ResultsGenetic testing revealed that both affected individuals (Ⅱ3 and Ⅱ5) carried compound heterozygous variants in the GBE1 gene: c.466C>T (p.R156C) in exon 4 and a large deletion of exons 3–7. The two pathogenic variants co-segregated in the family, confirming the diagnosis of APBD in these individuals.DiscussionThis case expands the phenotypic and genetic spectrum of APBD, particularly by documenting its occurrence in non-Ashkenazi Jewish patients. Additionally, the identification of atypical genetic alterations, such as the large deletion in GBE1, provides new insights into the genetic basis of the disease and may aid in understanding its broader clinical manifestations. These findings suggest the need for a broader genetic screening approach in APBD diagnosis, especially in diverse populations.